2020
DOI: 10.12659/msm.922497
|View full text |Cite
|
Sign up to set email alerts
|

MiR-423-5P Regulates Cells Apoptosis and Extracellular Matrix Degradation via Nucleotide-Binding, Leucine-Rich Repeat Containing X1 (NLRX1) in Interleukin 1 beta (IL-1β)-Induced Human Nucleus Pulposus Cells

Abstract: Background Disc degeneration is characterized partly by the degradation in the extracellular matrix (ECM) and excess apoptosis of nucleus pulposus (NP) cells. NLRX1 (nucleotide-binding, leucine-rich repeat containing X1) is different from the other nucleotide-binding-domain and leucine-rich-repeat proteins and mainly located to the mitochondrial. It negatively regulates NF-κB (nuclear factor kappa B) and apoptosis inhibition. However, how NLRX1 is regulated and exerts effects in disc degeneration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…NLRX1 has been shown to affect both. Overexpression of NLRX1 human nucleus pulposus cells in the intervertebral disc resulted in increased collagen synthesis and decreased ECM decomposing enzymes ( 103 ). On the other hand, Nlrx1- deficiency led to increased expression of wound healing factors epidermal growth factor (EGF) and TGFβ in epithelial cells in a mouse model of DSS-induced colitis ( 104 ).…”
Section: Discussionmentioning
confidence: 99%
“…NLRX1 has been shown to affect both. Overexpression of NLRX1 human nucleus pulposus cells in the intervertebral disc resulted in increased collagen synthesis and decreased ECM decomposing enzymes ( 103 ). On the other hand, Nlrx1- deficiency led to increased expression of wound healing factors epidermal growth factor (EGF) and TGFβ in epithelial cells in a mouse model of DSS-induced colitis ( 104 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found a three-fold downregulation in the expression of miR-423-5p in the BALF-derived exosomes from COPD patients as compared to healthy non-smoking controls. Of note, miR-423-5p is known to be involved in the regulation of apoptosis and extracellular matrix degradation in human nucleus pulposus cells [ 40 ]. Contrary to our findings, Molina-Pinelo et al (2014) identified increased expression of miR-423-5p in the BALF collected from COPD patients as compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…We found a 3-fold downregulation in the expression of miR-423-5p in the BALF-derived exosomes from COPD patients as compared to healthy non-smoking controls. Of note, miR-423-5p is known to be involved in the regulation of apoptosis and extracellular matrix degradation in human nucleus pulposus cells (44). Contrary to our findings, Molina-Pinelo et al (2014) identified increased expression of miR-423-5p in the BALF collected from COPD patients as compared to the control group.…”
Section: Discussionmentioning
confidence: 99%